Utopia and Ideal Theory: Reasons for a Divorce - Zuolo, Federico (Theoria (Pietermaritzburg), 2025)
In political theory, utopia is traditionally understood as representing a beautiful but impossible state of affairs. By contrast, the majority of scholarly works in utopian studies understand utopia not as a blueprint for a perfect society but as an indirect critique of the contemporary status quo. The aim of this article is to propose a distinction between utopias and ideal theories. To do so, the article adopts a working definition of utopias that emphasises the formal characters of utopian works (detailed narrative), and compares utopias with ideal theories, which are abstract in kind. After articulating this distinction through some paradigmatic examples (Plato, More, Rawls), the article argues that a better understanding of this difference may help us improve the debate. The article also argues that ideal theories, unlike utopias, are less tainted by the objection that ideals are practically irrelevant.